Science for all: museums as spaces of scientific dissemination - Angelo, Edna; Robalino, Juan (Educação, Escola & Sociedade, 2016)
The main task of the museum is to record aspects of the trajectory of man, character and agent of history. They are active and dynamic producers who create realities through objects. To promote the integration of scientific and technological work in the social fabric, stimulating reflection and debate, science museums use the three-dimensional material elements to implement communication with the visiting public. This article, through a bibliographical survey, tries to reflect the characteristics and peculiarities of the scientific divulgation in the specific environment of the museums. It is intended to answer the following questions: How can museums collaborate in the dissemination of science? It is concluded that museums dedicated to science contribute to the education of society and consequently to increase the interest in studying science or technology as a way to contribute to the wealth of the country in different senses. The dissemination of science, along with formal scientific education, is an essential element of overcoming underdevelopment and the social problems of the country. As a form of teaching, the museum can work in partnership with the emerging models of formal education, without any subservience to one another. It is presented as a way to favor the improvement of scientific education. He is an increasingly important actor in cities, in the country and in the world. Keywords: Information and Society. Scientific divulgation. Museums of Sciences.